The degree of the practice of the principals of the public schools in Ma’an governorate for leadership skills and ways of developing them from their point of view - Al-Jazi, Raida Abdel-Karim Da'san (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the degree of practice of the directors of the public schools for leadership skills in Ma’an governorate and ways of developing them from their point of view. To achieve the objectives of the study, the researcher used the descriptive approach .He constructed a tool for the study which consisted of (24) paragraphs and verified its validity and stability .A random sample consisted of (157) managers and directors.The results showed that the level of leadership of the public schools for leadership skills in Ma’an was high (4.05).The ranking of skills was ranked in descending order according to the level of areas: human skills, 4.12, technical skills, 4.09, , And reached (3.95).The results showed that there were no statistically significant differences at the level of (α = 0.05) in the degree of practice of the directors of the public schools for leadership skills in Ma’an governorate. In the light of the results, a number of recommendations and suggestions were presented to develop the leadership skills of the principals of the public schools in Ma’an and the whole of the Kingdom of Jordan.